Labor Mobility in Bolivia: On-the-job Search Behavior of Private and Public Sector Employees - Lykke E. Andersen; Bent Jesper Christensen (Institute for Advanced Development Studies (INESAD), 2006)
This paper estimates structural parameters of both a simple and an extended job separation model with the purpose of understanding constraints in the labor market in Bolivia. The results confirm the hypothesis that skilled labor is a scarce commodity in Bolivia, while unskilled labor is abundantly available. This implies that skilled employees shop around for alternative employment opportunities and quit their jobs when a better opportunity arises. The quit rate among skilled employees in the private sector is much higher than the quit rate among skilled employees in the public sector. The reverse is true for the lay-off rate, and together this suggests that the private sector has difficulties maintaining its skilled labor. The estimates of the wage sensitivity of job search effort parameters presented in this paper suggest that it would be difficult for the private sector to improve its capacity to retain skilled employees by increasing wages skilled employees in the private sector do not seem to reduce their on-the-job search in response to higher wages. The results are consistent with the hypothesis that the public sector in Bolivia, inflated by high levels of foreign aid (about 10% of GDP), may be detracting scarce human resources from local productive sectors, potentially jeopardizing the opportunity for sustainable development.
Keywords: J62; J63; J64; J31; 330; Mobility; on-the-job search; labor markets; Bolivia